Pengaruh Persepsi Kewirausahaan dan Efikasi Diri Terhadap Intensi Berwirausaha Mahasiswa Manajemen di Universitas Bandar Lampung - Airent, Ighea Clauvanza; Harpain (Jurnal EMT KITA, 2025)
This study aims to analyze the effect of entrepreneurial perceptions and self-efficacy on entrepreneurial intentions of management students at Bandar Lampung University. A quantitative approach was applied with data obtained through questionnaires distributed to 68 2021 students selected using the Slovin formula. Data analysis was conducted with multiple linear regression, where entrepreneurial perception and self-efficacy as independent variables, and entrepreneurial intention as the dependent variable. The results showed that both independent variables had a significant effect on students' entrepreneurial intention. This finding confirms the importance of strengthening entrepreneurial perceptions and self-efficacy to increase students' entrepreneurial intention. Practically, universities need to develop practice-based entrepreneurship programs, such as business training, mentoring with entrepreneurs, and business simulations. In addition, increasing self-efficacy can be done through activities that build confidence, such as leadership training and managerial skills development. Thus, educational institutions can create a more conducive environment for students to plan and start a business independently.